EFFECT OF RONDO TRAINING ON PASSING ACCURACY AND SHOOTING IN FOOTBALL FOR PLAYERS UNDER (14) YEARS OLD - Saleh, Haider Hussein (Journal Olahraga Rekat (Rekreasi Masyarakat), 2026)
Background. Rondo drills are a training method that integrates physical, technical, and tactical aspects in a simulated environment of real-life playing situations. These drills, conducted in small spaces with a limited number of players, focus on ball possession through short, quick passes. This forces players to make rapid decisions and accurately determine passing paths. Rondo drills are considered a modern training method in football, with many coaches referring to them as diverse and varied exercises. Objectives. Objectives of this study is to determine  influence of rondo practicing on under 14 players passing and shooting performance. Method. The researcher used a pre-test/post-test equivalent groups experimental design.  sample was 28 players less than 14 years from Al-Zawraa Sports club for  season of 2024-2025.  researcher homogenized  research sample, and then made it so that  equivalence between  two groups was based on  results of pre-tests of passing and shooting accuracy. We then applied Rondo training 3 days per week over a five-week period to  experimental group. Post-tests were carried out in similar conditions to  pre-tests. Results. The researcher analyzed  results to determine that rondo training showed a meaningful and beneficial impact on passing and shooting accuracy among  experimental group as opposed to those in in either of one-touch conditions. Additionally, the experimental group was significantly and independently better than control on accuracy of passing. Conclusion. Researcher suggests that rondo drills should be applied in  training (in warm-up and pre-game) to football players aged under 14 years, it could also be used as an exercise with youth and junior age groups in football.